E?cacy of Lignocaine and Esmolol in Attenuating the Cardiovascular Responses to Laryngoscopy and Endotracheal Intubation - Reddy, K Girish; Reddy, M Adithya; Babu, Ram (Academia Anesthesiologica International, 2020)
Background: The present study was undertaken to compare the efficacy of lignocaine and esmolol in attenuating the cardiovascular responses to laryngoscopy and endotracheal intubation. Subjects and Methods: 60 patients undergoing elective surgery were divided into two groups of 30 each, group L (Lignocaine) and group E (Esmolol). Baseline hemodynamic parameters - heart rate (HR), systolic blood pressure (SBP), diastolic blood pressures (DBP), mean arterial pressure (MAP) and rate-pressure product (RPP) were recorded. Results: There was no statistically significant difference in heart rate among the groups before and after premedication and after induction (P value >0.05). After intubation, there was rise in heart rate in both the groups. The rise was significantly less in esmolol group as compared lignocaine groups (p value <0.05) till 5 minutes of study period. There was no statistically significant difference in systolic blood pressure among the groups before and after premedication. After induction and intubation, there was no statistically significant difference in systolic blood pressure among the groups (p value >0.05). Conclusion: Esmolol hydrochloride 1mg/kg IV bolus dose is superior to lignocaine hydrochloride 1.5mg/kg IV bolus to attenuate the haemodynamic responses to laryngoscopy and endotracheal intubation.